Faktor Kebiasaan Tidak Menggunakan Alas Kaki dan Mencuci Tangan Berpengaruh terhadap Prevalensi Cacingan pada Anak Usia Sekolah Dasar - Permata, Reni; Junaiddin, Junaiddin; Untari, Untari (Health Information : Jurnal Penelitian, 2023)
Worms are one of the infections that occur in children, and cause the risk of worsening health with causative factors associated with WASH (water, sanitation, hygiene). This study aims to determine the effect of the habit of not using footwear and washing hands on the prevalence of worms in elementary school-age children in the Doom Islands, Sorong, West Papua. The research design used was a quasi-experimental pretest-posstest comparison group design, namely the entire case sample and control carried out fecal examination as a whole (pretest), then observation samples for 2 months and given health education treatment in the case group, and then re-stool examination (posttest). Sampling was carried out by the total sampling method with a total sample of 68 people. The results of the study found that there was an influence of the habit of not using footwear (p = 0.000) and the habit of not washing hands (p = 0.000) on the prevalence of worms in school-age children. The habit of not using footwear and the habit of not washing hands affect the prevalence of worms, so it is recommended to school principals to provide education related to PHBS to students.